ANALYSIS OF LABOR NEEDS USING THE RESOURCE LEVELING METHOD ON THE MAIN STRUCTURE OF HIGH-RISE BUILDINGS - Panjaitan, Nita Jesika; Putra, I Nyoman Dita Pahang (Komunitas Menulis dan Meneliti (Kolibi), 2024)
The distinctive characteristic of construction projects is that they involve a series of activities that are carried out once and within a specific timeframe. As project development progresses, there are limitations in the availability of resources, an imbalance in the workforce, sharp fluctuations, and the requirement for significant expenses. Labor and costs need to be analyzed based on existing qualifications throughout the project using the resource leveling method with the aid of Microsoft Project 2013 software to achieve more efficient and ideal results. Labor analysis is conducted based on real conditions on the field before and after the leveling process. The allocation before the leveling process experiences sharp fluctuations and exceeds the daily availability of labor. After the leveling process, the fluctuations are low, and the allocation obtained before the leveling process was 1575 people consisting of foremen, carpenters, masons, ironworkers, and laborers, resulting in a total cost of IDR 154,175,000. Meanwhile, after the leveling process, the labor obtained was 1540 people with the same qualifications as before leveling, resulting in a total cost of IDR 150,500,000, and the actual cost amounted to IDR 201,395,000. Thus, labor and costs after leveling produce the most efficient and ideal allocation.